Wild cats - Winston, Peggy D.; National Geographic Society (U.S.) ([Washington, D.C.] : National Geographic Society, 1981)
Brief text and photographs present the physical characteristics and behavior of various kinds of wild cats.
Keywords: Felidae -- Juvenile literature; Felidae; Cats